Dual Quaternion Blending Algorithm and Its Application in Character Animation - Xiang Feng; Wanggen Wan (Institute of Advanced Engineering and Science, 2013)
In this paper we generalize established techniques and blending algorithm for quaternions to dual quaternions to include all rigid transformations, and implement real-time character animation with dual quaternions under the platform of OpenGL. Classical quaternions are restricted to the representation of rotations although combination of matrix calculation and quaternions operator has been a popular tool in character animation since 1990s. In character animation and some other applications of 3D computer graphics, we are actually faced with rigid transformation which just includes translation and rotation. Similar to the way quaternions represent rotations, dual quaternions represent rigid transformations. Algorithms based on dual quaternions own better properties than those based on quaternions in practical applications, which include reduced overhead, increased computational efficiency and coordinate invariance.. Finally we demonstrate the effectiveness and superiority of dual quaternions blending algorithm by cartoon male and female mesh models with the animation of walking and waving. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3339